Chromium(VI) Heavy Metal Biosorption in Citarum River Water Sample Using Saccharomyces cerevisiae and Rhizopus oryzae Biomass - Suci Rizki Nurul Aeni; Ni'matul Murtafi'ah; Handarini Handarini (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
The Citarum River was regarded as the World’s dirtiest river in 2018, characterized by a Basin situated adjacent to several textile and electroplating industries. Hexavalent chromium metal (Cr6+) is a toxic, carcinogenic heavy metal found in the wastes of these industries. Furthermore, biosorption with biological adsorbents, including Saccharomyces cerevisiae and Rhizopus oryzae, is an alternative method for treating water polluted with heavy metals. This study therefore aims to adsorb Cr6 + heavy metals from Citarum River water using S. cerevisiae and R. oryzae biomass in two locations: Nanjung and Pangauban, with various biomass concentration and stirring speeds. For this study, 0.25, 0.5, and 0.75 g of R. oryzae suspension, as well as 250, 500, and 750 µ of S. cerevisiae were used as adsorbent, while rotated at speeds of 250 rpm, 750 rpm and 1500 rpm. Subsequently, the Cr6 + metal content was measured using a UV-Vis spectrophotometer at a wavelength of 525 nm, and calculated based on a standard curve. The results showed S. cerevisiae and R. oryzae are able to reduce the levels of Cr6+ in Citarum river water. The most reduction was obtained with the highest concentration of the adsorbents, 750 µ for S. cerevisiae and 0.75 g for R. oryzae, at the speed of 1500 rpm. S. cerevisiae and R. oryzae have great potential as biosorbents for the in situ remediation of Citarum River contaminated with heavy metals.